Peran Pelatihan K3 dalam Mendukung Pemanfaatan Insinerator bagi Pengelolaan Sampah Masyarakat - Antesty, Sella; AP, Yuhendra; Mi’raj Fuadi; M. Azhar Mustafid; Wiwin Apriyanditra; Amuddin; Fakhrul Irfan Khalil; Wahyudi Zulfikar; Rahman Yazid Tabrani (Universitas Mataram, 2025)
This community engagement program aimed to strengthen occupational safety and health (OSH) practices in waste management through the introduction of a large-scale incinerator in Pakuan Village, West Nusa Tenggara, Indonesia. The activity combined direct instruction with the distribution of a practical manual that serves as a long-term operational guide for the community. In addition, the provision of personal protective equipment (PPE) was integrated into the program to enhance the safety of machine operators and reduce potential exposure to hazardous pollutants. The results indicate that participants gained a clearer understanding of incinerator operation, safety protocols, and preventive measures, enabling them to apply waste-to-energy technology more responsibly. Beyond its technical benefits, the program fostered a culture of safety and accountability among local residents, demonstrating the importance of combining training, written guidelines, and protective facilities in sustaining community-based waste management initiatives. This approach highlights the potential of university–community collaboration in promoting environmentally sound and socially responsible waste management practices.